Education Human Excellence - Aminul Wathon (EDUCATIO : Journal of Education, 2018)
In line with the logic of ecology and the philosophy of Existentialism, the existence of one thing is always in the company of one or more of other things. This, to give a correct idea or to avoid misunderstandings of the use of the predicate ahead as in terms like seeds, superior schools, excellent products of education, and others, it is morally imperative for the users of such terms to provide the terms with Reviews their Contexts to Determine Whether a superior means 'prime', 'superior', 'competitive', or any other. Instances of such Contexts can be of appearance or performance, of a long or short term, of the current objectives or future goals, of individuals or the community, of individual or social needs, of national or international needs, of inclusive or exclusive purposes, and others. Even now, the writer is still of the belief that the usage of the aforementioned Reviews those terms in the field of education in Indonesia is still more as jargon rather than basic concepts. Indeed very rarely or even never does the public, particularly subject to Reviews those who are very much concerned with the development of education in Indonesia, to get a thorough explanation of Reviews those terms Mentioned. This article tries to build a kind of "second opinion" as a balance to the existence of that jargon Mentioned.